Functional genomic analysis reveals overlapping and distinct features of chronologically long-lived yeast populations - Wierman, Margaret B. (Aging (Albany NY), 2015)
Yeast chronological lifespan (CLS) is extended by multiple genetic and environmental manipulations, including caloric restriction (CR). Understanding the common changes in molecular pathways induced by such manipulations could potentially reveal conserved longevity mechanisms. We therefore performed gene expression profiling on several long-lived yeast populations, including an ade4∆ mutant defective in de novo purine (AMP) biosynthesis, and a calorie restricted WT strain. CLS was also extended by isonicotinamide (INAM) or expired media derived from CR cultures. Comparisons between these diverse long-lived conditions revealed a common set of differentially regulated genes, several of which were potential longevity biomarkers. There was also enrichment for genes that function in CLS regulation, including a long-lived adenosine kinase mutant (ado1∆) that links CLS regulation to the methyl cycle and AMP. Genes co-regulated between the CR and ade4∆ conditions were dominated by GO terms related to metabolism of alternative carbon sources, consistent with chronological longevity requiring efficient acetate/acetic acid utilization. Alternatively, treating cells with isonicotinamide (INAM) or the expired CR media resulted in GO terms predominantly related to cell wall remodeling, consistent with improved stress resistance and protection against external insults like acetic acid. Acetic acid therefore has both beneficial and detrimental effects on CLS.